The educational significance of engagement with diversity - Sardoč, Mitja (Dve domovini, 2012)
This article examines the issue of engagement with diversity and the various problems, tensions and challenges we are likely to encounter when including diversity in classrooms and other educational settings. The introductory section of this article deals with some preliminary considerations associated with the educational significance of engagement with diversity. I then introduce the three basic dimensions of diversity we are likely to encounter when discussing inclusion of diversity in any non-ideal educational environment. In Section III I examine the educational signifi cance of engagement with diversity and identify the diff erent functions engagement with diversity performs. In Section IV I examine the main controversies and the associated shortcomings any intuitive account of engagement with diversityis likely to face. In the conclusion, I specify how we should understand the idea of the fair treatment of engagement with diversity which is consistent with the commitment of educating students so as to recognise and respect one another as free and equal members of a polity.
Keywords: civics; državljanska vzgoja; education; izobraževanje; pluralism (social sciences); pluralizem (družbene vede); večkulturnost; vzgoja